RIJOQ: Attraction in the Maintenance of the Tunjung Language from Threat of Extinction - Aquari Mustikawati; Nurul Masfufah (Tradition and Modernity of Humanity, 2023)
The Tunjung language in Barong Tongkok District, West Kutai holds a wealth of knowledge and culture of its people. However, during the development, the vitality of Tunjung language has decreased and held an endangered status. Therefore, it needs revitalization efforts, one of the them is through local art of RIJOQ, that is Tunjung language folk song. The purpose of this research is to describe the form of RIJOQ and the strategy of revitalizing the Tunjung language through RIJOQ. Data collection was carried out by interview and literature study methods. Interviews were conducted by structured interviews with respondents based on prepared guidelines. The literature study was carried out using note-taking techniques in the form of RIJOQ lyrics data from documentation in the form of books and social media. The data analysis used a descriptive method with an anthropolinguistic approach. The findings from the results of this study are that the form of poetry and contents of RIJOQ has shifted from traditional to modern; there are extensions and additions to themes, such as romance, affairs, household; using everyday words that are easy to understand; with simpler structure. These findings serve as a reference for the revitalization process of the Tunjung language. The values contained in RIJOQ include belief, wise advice, mutual respect, mutual forgiveness, honesty, patience, and responsibility. The revitalization strategy is to provide space for peRIJOQ or singer of RIJOQ, especially the younger generation, by holding performances in traditional and official events, celebration by holding competitions regularly; provide guidance to RIJOQ groups in order to preserve the Tunjung culture and language; social control over the development of RIJOQ; conduct studies on RIJOQ, and popularize RIJOQ through media, such as radio, television, cd, Youtube, Facebook, Instagram, dan Google Play. Thus, the existence of RIJOQ not only provides a special attraction for the younger generation but also to preserve the Tunjung language.